Agents' Abilities - Jaster, Romy (Philosophical Analysis, 2020)
What is it for agents to be able to do things? This question, while central to many debates, is still awaiting a comprehensive answer. Jaster provides just that by developing the "success view," which posits that abilities are in essence a matter of successful behavior. Along the way, she explores various issues, including the augmentable nature of abilities, the relationship between abilities and dispositions, and the ability to act otherwise.